Performance improvement of FSO system using multi‐pulse pulse position modulation and SIMO under atmospheric turbulence conditions and with pointing errors. Issue 4 (1st July 2018) - Ismail, Tawfik; Leitgeb, Erich; Ghassemlooy, Zabih; Al‐Nahhal, Mohamed
Abstract : Free space optics (FSO) communication links are impaired by the fading due to turbulence and misalignment. In this paper, we theoretically analyze the pointing error effects on performance of FSO systems using multi‐pulse pulse position modulation (MP‐PPM) over the Gamma‐Gamma turbulence channel. We consider the moderate and strong atmospheric turbulence regimes with the combined effect of the pointing errors (PEs), and study the link average symbol error rate (ASER) and the outage probability. The numerical results are presented to show the impact of the pointing error on the ASER and the system outage. However, to overcome the channel degradation resulting from the turbulence effects and the PE, the single‐input multiple‐output (SIMO) system with maximal ratio combining (MRC) diversity is used. Exact close‐form expressions for ASER and outage probability are derived and verified by using Monte Carlo simulation. We concluded that the optimal values of the system parameters are, the transmitted power is 20 dBm, jitter variance should be less than 0.5 m and laser beam width equals 0.2 cm. These values are significantly reduced the impacts of misalignment and fading whereas outage probability is less than at maximum jitter variance.